PERUBAHAN SOSIAL PETANI KARET DI DESA BONGKAL MALANG KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Anggi Pratiwi; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in The Bongkal Malang Village Of Kelayang Sub-district. The purpose of this research is to analyze the aspects of social change happens on the rubber farmers now compared to the past of The Bongkal Malang Village Of Kelayang Sub-district. This study entitled "The Social change Rubber Farmers in The Bongkal Malang Village Of Kelayang Sub-district of Indragiri Hulu regency". The focused topic of the research is problem what is faced by a rubber farmers in The Bongkal Malang Village Of Kelayang Sub-district of Indragiri Hulu regency. The sample in this research is the rubber farmers in The Bongkal Malang Village Of Kelayang Sub-district totaled 92 heads of families. As for the sampling method by using a sampling of saturated (census) is the technique of determination of the sample when all members of a population is used as the sample according to (Sugiyono 2008,2009,2010:68). The author uses descriptive quantitative methods will then be presented empirical evidence based on interviews, questionnaires and observations in field. The results showed a rubber Farmer social changes In social aspects based Bongkal Village consists of social life, social interaction and social status. For the past social life are categorized either, because most of the respondents who are always concerned with the lives of his fellow farmers in particular and society in General. And social interaction of the past even better good of the present, because most of the respondents always interacted socially sasama farmers especially and the community at large. While the social status of the present is better than the past, because most of the respondents already have adequate earnings and a good life. Economic aspects, namely livelihood today is better than the past, because most of the respondents already focuses to farmed rubber, besides having a livelihood moonlighting to make extra income.Keywords: Social Change, A Rubber Farmer